2016
DOI: 10.1038/srep28660
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocholine – an agonist of metabotropic but not of ionotropic functions of α9-containing nicotinic acetylcholine receptors

Abstract: We demonstrated previously that phosphocholine and phosphocholine-modified macromolecules efficiently inhibit ATP-dependent release of interleukin-1β from human and murine monocytes by a mechanism involving nicotinic acetylcholine receptors (nAChR). Interleukin-1β is a potent pro-inflammatory cytokine of innate immunity that plays pivotal roles in host defence. Control of interleukin-1β release is vital as excessively high systemic levels cause life threatening inflammatory diseases. In spite of its structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(195 citation statements)
references
References 47 publications
16
173
0
6
Order By: Relevance
“…These results are in line with the idea that chemokine signaling triggers a recently described mechanism involving activation of metabotropic functions of noncanonical nAChR containing subunits α 7 and α 9 that inhibit P2X7 signaling and, consequently, BzATP-induced release of IL-1 β [18, 20]. Of note, the inhibitory effect of acetylcholine (10  μ M) was not impaired by silencing of CCR expression (Figure 3(c)), suggesting that nAChR are acting downstream of CCR.…”
Section: Resultssupporting
confidence: 88%
“…These results are in line with the idea that chemokine signaling triggers a recently described mechanism involving activation of metabotropic functions of noncanonical nAChR containing subunits α 7 and α 9 that inhibit P2X7 signaling and, consequently, BzATP-induced release of IL-1 β [18, 20]. Of note, the inhibitory effect of acetylcholine (10  μ M) was not impaired by silencing of CCR expression (Figure 3(c)), suggesting that nAChR are acting downstream of CCR.…”
Section: Resultssupporting
confidence: 88%
“…In our study the acute inhibition of M2R in the trachea almost doubled the increase in PTS after stimulation of brush cells with bitter tasting substances. 14,51,52 In conclusion, the present findings reveal that the whole transcriptome of tracheal epithelial BC is distinct to that | 331 HOLLENHORST ET aL. 16 Additionally, ACh mediates important innate immune functions after being released from BC, for example, induction of protective respiratory reflexes.…”
mentioning
confidence: 68%
“…The α9 and α10 subunit transcripts have been identified in immune cells, including lymphocytes, neutrophils, and monocytes (36). It has also recently been shown that functional α9α10 nAChRs regulate ATP-dependent cytokine release in monocytes (37) and that α9-containing nAChRs modify the function of proinflammatory monocytes (38). The α9-containing nAChRs also modulate the influx of monocytes and neutrophils in experimental autoimmune encephalomyelitis, a murine model of multiple sclerosis (39,40).…”
Section: Discussionmentioning
confidence: 99%